Security in new concepts of software defined networks - Gameiro, Ana Maria Ferreira (2019)
Nowadays, everything is recorded and shared using electronic devices. However, most people don’t apply security measures to safeguard their information. This is a major problem in the enterprise environment since people go to work and connect their devices to their company’s network. It takes only one infected smartphone or computer to compromise the entire company. Therefore, security is a crucial point in a business’ management, especially regarding its network. But this is not an easy thing to do since the security field is constantly changing and evolving to overcome problems and vulnerabilities that are discovered every day. The work to be presented is one that attempts to overcome some of these problems. It uses Software Defined Networking (SDN) concepts to improve network security in the enterprise environment. This thesis presents a system with several security elements, each one tackling a different problem. Making use of honeypots technology, the system developed not only identifies attacks but can also create decoys to attackers in order to extract information to improve the already existing security measures.